Meet them where they are: the importance of contextual relevance in prison-based parenting programs - Henson, Abigail (The prison journal, 2020)
Parenting from prison is dramatically different than parenting in the community. The removal from home and redefinition of self that occurs within the carceral setting often leads incarcerated parents to feel anxious and inadequate in their parental role. While some prison-based parenting programs (PBPPs) can assuage these issues, they often lack contextual relevance, which can make participants frustrated and dissatisfied. Using an example of a prison-based fatherhood program, this article argues that in order for PBPPs to have sustained positive outcomes, they must also address the issues enmeshed in parenting from prison